Revitalizing myocarditis treatment through gut microbiota modulation: unveiling a promising therapeutic avenue - Wang, Jingyue; Zhang, Xianfeng; Yang, Xinyu; Yu, Hang; Bu, Mengmeng; Fu, Jie; Zhang, Zhengwei; Xu, Hui; Hu, Jiachun; Lu, Jinyue; Zhang, Haojian; Zhai, Zhao; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Numerous studies have demonstrated that gut microbiota plays an important role in the development and treatment of different cardiovascular diseases, including hypertension, heart failure, myocardial infarction, arrhythmia, and atherosclerosis. Furthermore, evidence from recent studies has shown that gut microbiota contributes to the development of myocarditis. Myocarditis is an inflammatory disease that often results in myocardial damage. Myocarditis is a common cause of sudden cardiac death in young adults. The incidence of myocarditis and its associated dilated cardiomyopathy has been increasing yearly. Myocarditis has gained significant attention on social media due to its association with both COVID-19 and COVID-19 vaccinations. However, the current therapeutic options for myocarditis are limited. In addition, little is known about the potential therapeutic targets of myocarditis. In this study, we review (1) the evidence on the gut-heart axis, (2) the crosslink between gut microbiota and the immune system, (3) the association between myocarditis and the immune system, (4) the impact of gut microbiota and its metabolites on myocarditis, (5) current strategies for modulating gut microbiota, (6) challenges and future directions for targeted gut microbiota in the treatment of myocarditis. The approach of targeting the gut microbiota in myocarditis is still in its infancy, and this is the study to explore the gut microbiota-immune system-myocarditis axis. Our findings are expected to pave the way for the use of gut microbiota as a potential therapeutic target in the treatment of myocarditis.